Ответы и объяснения

2013-02-22T17:56:45+00:00

cos3x=cosx*(4cos^2 x-3)

cosx+cos3x=cosx+cosx*(4cos^2 x-3)=cosx*(1+4cos^2 x-3)=cosx*(4cos^2 x-2)=2cosx*(2cos^2 x-1)=2cosx*cos2x

 cosx+cos3x+((корень из 3)cosx+sinx)cosx= 2cosx*cos2x+((корень из 3)cosx+sinx)cosx=cosx*(2cos2x+(корень из 3)cosx+sinx)=0

cosx=0, x=П/2+Пn, n принадлежит Z

2cos2x+(корень из 3)cosx+sinx=0

2cos2x+2*( (корень из 3)/2*cosx+1/2*sinx)=0

2cos2x+2*(cos(п/6)*cosx+sin(п/6)*sinx)=0

2cos2x+2cos(x-п/6)=0

cos2x+cos(x-п/6)=0

2cos((3x-п/6)/2)*cos((x+п/6)/2)=0

a) cos((3x-п/6)/2)=0

 (3x-п/6)/2=П/2+Пk

  3x- п/6=П+2Пk

  3x=7П/6+2Пk

  x=7П/18+2Пk/3

b) cos((x+п/6)/2)=0

   (x+п/6)/2=П/2+Пk

    x+п/6=П+2Пk

    x=5П/6+2Пk

Ответ:  x=П/2+Пn; 7П/18+2Пk/3; 5П/6+2Пk    n,k принадлежит Z